Resilience and Mental Health in the Polish Population during the COVID-19 Lockdown: A Mediation Analysis - Janusz Surzykiewicz (MDPI AG, 2021)
The aim of this paper was to assess the state of resilience and well-being in the Polish population during the COVID-19 pandemic. We also assessed the relationship between resilience and mental health. Finally, we tested the mediating role of COVID-19 anxiety, persistent thinking, and the stress burden in the relationship between mental health and resilience. This research perspective can provide important insights into how individuals can become mentally stronger during the COVID-19 pandemic. Methods: This study included 1758 people (73% women) aged 18–80 years. The procedure consisted of completing a questionnaire measuring well-being, COVID-19 anxiety, obsession with COVID-19, stress over COVID-19, and resilience. Results: Bootstrap sampling analysis showed significant partial mediators for the relationship between resilience and well-being. Important mediators were coronavirus anxiety, persistent thinking, and perceived stress. Conclusions: The results of the present study clearly indicate that resilience as a protective factor is associated with reduced anxiety about COVID-19, perceived stress burden, obsessive thoughts about the pandemic, and increased well-being of individuals. Resilience plays an important role in minimizing negative and enhancing positive health indicators in the face of challenging life events.